The Concept of Islamic Education as a Scientific Discipline - Siti Aminah; Sinta Rahmatil Fadhilah (Postgraduate Studies UIN Sulthan Thaha Saifuddin Jambi, 2020)
This paper considering that education is the main source of development. Education always provides updates and development. As a religion that is very existential among mankind, Islam contributes to education. As an applied science, Islamic education has relations to knowledge and humans. Thus, Islamic Education is one of the scientific disciplines that specifically exist among other scientific disciplines. If Islamic education is a scientific discipline, it must be scientifically academic. Even though it is academic, Islamic education is not subject to modern culture that tends to be anti-religious. Islamic education still prioritizes the al-Qur'an, Sunnah, the opinions of the prophet’s companionships, ulama's, and Muslim scientists as the main sources. This paper aims to describe Islamic education as a scientific discipline. This paper is based on library research whose main source is writings related to Islamic education and scientific disciplines, as well as other relevant writings to be references in this paper. Tulisan ini berawal dari kesadaran bahwa pendidikan merupakan sumber pokok suatu perkembangan. Pendidikan selalu memberikan pembaharuan dan mengalami perkembangan. Sebagai salah satu Agama yang sangat eksistensial pada kalangan umat manusia, Islam memberikan kontribusi dalam hal pendidikan. Sebagai ilmu terapan pendidikan Islam memilki keterikatan antara pengetahuan dengan manusia, sehingga Ilmu Pendidikan Islam sudah tentu sebagai salah satu disiplin keilmuan yang khusus berdiri di antara disiplin keilmuan yang lain. Jika pendidikan Islam sebagai suatu disiplin ilmu maka pendidikan Islam harus bersifat ilmiah akademik, walaupun bersifat akademis pendidikan Islam tidak tunduk kepada budaya modern yang cenderung anti agama. Pendidikan Islam tetap menjadikan al-Qur’an, Sunah, pendapat para sahabat, ulama, dan ilmuan muslim sebagai sumber utama. Sehingga tulisan ini bertujuan untuk menguraikan tentang pendidikan Islam sebagai suatu disiplin ilmu. Tulisan ini berbasis penelitian pustaka yang sumber utamanya adalah tulisan-tulisan terkait pendidikan Islam dan disiplin ilmu, serta tulisan lain yang relevan yang menjadi rujukan dalam tulisan ini.